Expectancy Violations terhadap Persepsi pada Setting Tempat Tinggal: Studi Eksperimental - Yasmin Nursyabina Bakri; Izzatush Shafa Aina; Amira Rasyanda Alifa; Keshia Ezra; Zharifa Anisa Widiyansari; Wilis Srisayekti; Risa Dwi Ratnasari (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
Perception is influenced by four factors; beliefs, values, social influence and expectations. Expectations which affect perceptions are divided into two; expectancy violations and expectancy non-violations.  There is a difference in reaction time in perception when expectations match and when they do not match with reality. Treatment was given to a group of 78 college students, in the form of giving perceptions and expectations. Within participants post-test only design was used to see the difference in reaction times of the two treatments. Expectancy violations have a significant influence on the perception time of the participants. This can be caused by past experience which formed expectations, as well as the room layout in the partisipants' own residence.